DESAIN LKPD BERORIENTASI PEMBELAJARAN TERPADU TIPE JARING LABA-LABA UNTUK PEMBELAJARAN IPA KELAS VIII SMPN 1 PAINAN - Randi Hidayat; Festiyed Festiyed; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2016)
Integrated science learning in 2013 curriculum should be conducted by teacher in Junior High School. In this case, the student worksheet is required to support the integrated science learning. But integrated science learning can’t be implemented well. As solution of this problem is to design student worksheet that orient webbed model. The objective of this research is to determine the description, validity, practicality, and effectiveness of this student worksheet. Type of this research is the research and development or R & D. As research design is before and after of treatment. There are three instruments to collect the data namely validity sheet, practicality sheet and student competence sheet. Technique of data analysis in this research is compare mean test. There are two results of this research. First, student worksheet consist of title, manual learning, competency to be achieved, learning material, support information, learning material discussion, assigment, work prosedures, and evaluation. Validity of student worksheeet can be categorized into very valid with average validity value is 80.38. Second, implementation of student worksheet is practice in integrated science learning. On the other hand, student worksheet is effective implemented in integrated science learning